O ensino da matemática para alunos surdos: metodologias para os primeiros anos do ensino fundamental - Campos, Lívia Rezende Miranda (2021)
This research aimed to answer the following question: given the development of deaf students as active beings in the construction of his/her own knowledge, which methodologies are more appropriate to teach mathematics to them in the first years of elementary school? Moreover, the general objective of this investigation was to study, identify and analyze the most appropriate methodologies for teaching mathematics to deaf people in the first years of elementary school, in order to recognize them as active beings in the knowledge development. To answer the research problem and achieve the intended objectives, at first, it was developed a theoretical study that subsidizes all the work, discusses and analyzes: theoretical and practical considerations about the teaching and learning of Mathematics in the early years of elementary school; conceptions and definitions related to deafness; relations between teaching, learning, deafness, language and mathematics; training of the teacher who teaches mathematics in the first years of elementary school; methodological alternatives for the teaching in this level of education; and methodologies in the teaching of mathematics in the early years of elementary school, from an inclusive education perspective of deaf subjects. In the second moment, a survey was carried out in the database of the Brazilian Digital Library of Theses and Dissertations and in the Catalog of Theses and Dissertations of the Higher Education Personnel Coordination Portal (BDTD and Portal CAPES, in Portuguese abbreviation), with the intention of obtain investigations related to methodologies, mathematics and deaf students in the first years of elementary school. From the data collection, the research developed a meta-analysis work, with a qualitative approach (BICUDO, 2014; FIORENTINI; LORENZATO, 2007), in order to describe and analyze the studies that dealt with the aforementioned themes. The results pointed out that the methodologies in the teaching of Mathematics for deaf people should meet the needs of the target audience and be mediated by Brazilian Signal Language (Libras, in Portuguese abbreviation). Thus, it was possible to verify that some methodologies, with the combination of the aforesaid criteria, may be more appropriate for teaching mathematics to deaf students, namely: techniques that explore the visual aspect, digital resources, manipulable materials and games; methodologies that explore social reality and contemplate the culture of deaf people, mathematical research, scenarios for investigation and problem solving; methodologies that promote interaction, communication, involvement and effective student participation, games, mathematical research, technologies applied to mathematical education (educational software) and manipulable materials; and methods that encourage bilingualism and the inclusion of deaf students.